A cobalt (II) complex with 6-methylpicolinate: Synthesis, characterization, second- and third-order nonlinear optical properties, and DFT calculations. (November 2016) - Altürk, Sümeyye; Avcı, Davut; Tamer, Ömer; Atalay, Yusuf; Şahin, Onur
Abstract: A cobalt(II) complex of 6-methylpicolinic acid, [Co(6-Mepic)2 (H2 O)2 ]·2H2 O, was prepared and fully determined by single crystal X-ray crystal structure analysis as well as FT-IR, FT-Raman. UV–vis spectra were recorded within different solvents, to illustrate electronic transitions and molecular charge transfer within complex1 . The coordination sphere of complex1 is a distorted octahedron according to single crystal X-ray results. Moreover, DFT (density functional theory) calculations with HSEH1PBE/6-311 G(d, p) level were carried out to back up the experimental results, and form base for future work in advanced level. Hyperconjugative interactions, intramolecular charge transfer (ICT), molecular stability and bond strength were researched by the using natural bond orbital (NBO) analysis. X-ray and NBO analysis results demonsrate that O−H···O hydrogen bonds between the water molecules and carboxylate oxygen atoms form a 2D supramolecular network, and also adjacent 2D networks connected by C−H···π and π···π interactions to form a 3D supramolecular network. Additionally, the second− and third−order nonlinear optical parameters of complex1 were computed at DFT/HSEH1PBE/6-311 G(d, p) level. The refractive index ( n ) was calculated by using the Lorentz−Lorenz equation in order to investigate polarization behavior of complex1 in different solvent polarities. The first−order static hyperpolarizability (β) value is found to be lower than pNA value because of the inversion symmetry around Co (II). But the second−order static hyperpolarizability (γ) value is 2.45 times greater than pNA value (15×10 −30 esu). According to these results, Co(II) complex can be considered as a candidate to NLO material. Lastly molecular electrostatic potential (MEP), frontier molecular orbital energies and related molecular parameters for complex1 were evaluated. Graphical abstract: Highlights: Co(II)−6-Mepic complex was synthesized. Its coordination sphere is a distorted octahedral geometry. Vibrational properties were investigated by FT-IR, FT-Raman spectra. UV−vis spectra were recorded in different solvents. The second- and third-nonlinear optical parameters were obtained by DFT level.